2018
DOI: 10.1071/cp17214
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and comparative analysis of NBS-LRR resistance genes in Brassica napus

Abstract: Plant disease-resistance genes play a critical role in providing resistance against pathogens. The largest family of resistance genes are the nucleotide-binding site (NBS) and leucine-rich repeat (LRR) genes. They are classified into two major subfamilies, toll/interleukin-1 receptor (TIR)-NBS-LRR (TNL) and coiled-coil (CC)-NBS-LRR (CNL) proteins. We have identified and characterised 641 NBS-LRR genes in Brassica napus, 249 in B. rapa and 443 in B. oleracea. A ratio of 1 : 2 of CNL : TNL genes was found in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
76
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 77 publications
16
76
1
Order By: Relevance
“…The uneven distribution of TNLs and CNLs is not uncommon in other plant species [30,31,32,33]. The vast majority of TNLs and CNLs appeared in clusters of 2 to 10 TNLs and CNLs, which is similar to the results of previous studies in B. napus [29], Arabidopsis, Medicago truncatula and Solanum tuberosum [30,34,35].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The uneven distribution of TNLs and CNLs is not uncommon in other plant species [30,31,32,33]. The vast majority of TNLs and CNLs appeared in clusters of 2 to 10 TNLs and CNLs, which is similar to the results of previous studies in B. napus [29], Arabidopsis, Medicago truncatula and Solanum tuberosum [30,34,35].…”
Section: Discussionsupporting
confidence: 88%
“…RNLs are likely derived from the CNL lineage [27,29]. The function of RNLs is yet to be determined, but they have no direct response to the pathogen and may have not the same duplication rates as TNLs and CNLs, which explains their lower abundance in the genome [27,29]. They may have a role in defence-signal transduction [38] or as helpers of other NBS genes [38].…”
Section: A Previous Phylogenetic Analysis Of Ntnls and Cnls From Fivementioning
confidence: 99%
“…TNLs were found to be more abundant than CNLs. The greater number of TNLs compared with CNLs has been previously reported in B. napus (Alamery, ; Alamery et al ., ), B. rapa , Arabidopsis (Meyers et al ., ; Mun et al ., ; Yu et al ., ) and Linum usitatissimum (linseed) (Kale et al ., ). It has been reported that the TIR domain is an important component of innate immunity across species through self‐association and ligand‐specific protein–protein interactions (Ve et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…For example, Alamery et al . () found 641, 443 and 249 NBS‐LRR genes in B. napus , B. oleracea and B. rapa , respectively, while Yu et al . () identified 157, 206 and 167 NBS‐LRR genes in B. oleracea , B. rapa and A. thaliana , respectively, which may be due to using different approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation